AUKUS-RI: The Answer for Indonesia’s Future Maritime Challenges Over the North Natuna Sea? - Nurjanah, Ita; Silaen, Christo Ariel Mario (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study explores Indonesia's maritime security challenges in the North Natuna Sea (NNS) amid rising tensions in the South China Sea, driven by major power rivalries, particularly China's assertiveness and the implications of the AUKUS trilateral security pact. Study Design/Methodology/Approach: The research employs a literature review and meta-analysis to synthesise existing studies on Indonesia’s defence policy and maritime strategy, offering a comprehensive examination of the nation’s strategic responses to external pressures. Findings: The findings reveal that Indonesia faces critical challenges in safeguarding its sovereignty over its Exclusive Economic Zone (EEZ) due to China’s aggressive territorial claims and military activities. Additionally, the emergence of AUKUS has encouraged Indonesia to reassess its security posture, indicating a potential pivot towards deeper defence cooperation with Western allies and modernising its military capabilities. Originality/Value: This research contributes to the discourse on maritime security in Southeast Asia by addressing Indonesia's strategic options and examining the potential significance of an AUKUS-Republic of Indonesia partnership (AUKUSRI). It underscores the importance of adaptive measures to navigate an increasingly complex geopolitical landscape.